Efficacy of erythropoietin as a neuroprotective agent in CKD-associated cognitive dysfunction: A literature systematic review - Michelangela Barbieri; Paolo Chiodini; Piergiacomo Di Gennaro; Gaye Hafez; Sophie Liabeuf; Jolanta Malyszko; Laila-Yasmin Mani; Francesco Mattace-Raso; Marion Pepin; Norberto Perico; Mariadelina Simeoni; Carmine Zoccali; et al. (Elsevier, 2024)
Patients with chronic kidney disease (CKD) often experience mild cognitive impairment and other neurocognitive disorders. Studies have shown that erythropoietin (EPO) and its receptor have neuroprotective effects in cell and animal models of nervous system disorders. Recombinant human EPO (rHuEPO), commonly used to treat anemia in CKD patients, could be a neuroprotective agent. In this systematic review, we aimed to assess the published studies investigating the cognitive benefits of rHuEPO treatment in individuals with reduced kidney function. We comprehensively searched Pubmed, Cochrane Library, Scopus, and Web of Science databases from 1990 to 2023. After selection, 24 studies were analyzed, considering study design, sample size, participant characteristics, intervention, and main findings. The collective results of these studies in CKD patients indicated that rHuEPO enhances brain function, improves performance on neuropsychological tests, and positively affects electroencephalography measurements. These findings suggest that rHuEPO could be a promising neuroprotective agent for managing CKD-related cognitive impairment.